Offshore Companies in the International Movement of Capital - K. G. Tatulov (Vestnik MGIMO-Universiteta)
In this article the author makes a brief quantitative and feature analysis of the role of offshores in the world economy. He gives the definition for offshores and considers the possibility to estimate the real scale of offshore activity. The author also points out the positive and negative consequences of use of offshores by economic agents.